SALAM DAN KINESIK DALAM BEBERAPA BAHASA - Sonezza Ladyanna (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
Greetings, along with its kineses, vary from one language to another, showing the culture of the speakers. This article discusses the system of greetings with their kineses in several languages from different continents. The research was conducted by taking into account some environmental, geographical, and socio-cultural factors of the users of the languages. The method of the research is a combination of some linguistic methods and cultural methods. The use of greetings in Indonesian, Korean, Arabic, Hungarian, Spanish, Swedish, and Swahili has a relationship with the natural state of the speakers. The greeting system in relation to the time of morning, afternoon, evening, and night can be classified into two classes. People living in areas with the time division of the morning, afternoon, evening, and night tend to use clear time-based greeting.